Reference Rot in theses: a HiberActive pilot - Osborne, Nicola (My University, 2017)
The Reference Rot in theses: a HiberActive pilot is a short University of Edinburgh-funded project to explore how the principles of using “Hiberlinks” in scholarly work can be applied in practice. We are working to develop practical tools to support PhD students ensure that when they cite a URL in their thesis (or in chapters, associated publications, etc.) it remains valid and useful rather than suffering from “Reference Rot”. The project builds on the EDINA and Los Alamos Hiberlink research (as presented at Repository Fringe 2010; Open Repositories 2012) which highlighted the issues of Reference Rot and the potential use of “decorated” URLs to ensure original and time stamped archives of web materials are cited in one place. Now, working with postgraduate intern researchers, we have been exploring the needs of PhD students across the University of Edinburgh to better understand how much they think about the persistence of web materials – particularly once they complete and deposit their thesis, and what kind of information and support they require to use Hiberlinks in their own work. We are also working with local colleagues working with repositories and theses to understand how best to integrate these approaches in the pre/deposit stages. In this short 10x10 we will share an overview of our work and share some of our findings and the pilot tools we have created. We think this work has huge potential and welcome feedback and further discussion after the presentation and will provide links to the pilot tools for further explorations.
Keywords: reference rot